Key challenges in the current TB & HIV information system in South Africa : a case study in Khayelitsha, Western Cape - Koivu, Annariina (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2015)
South Africa has one of the most serious human immunodeficiency virus (HIV) / and tuberculosis (TB) epidemics in the world, with high incidence, prevalence and co-infection rates. Information is at the heart of managing the TB and HIV epidemics, both inside and outside healthcare facilities. All stakeholders including the general public, patients, health professionals and policy-makers need access to valid, complete and up-to-date information in order to make choices and decisions (HIQA, 2013). Yet, this goal is not often met in developed countries and almost never in developing ones.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin